Oophorectomy and rate of dementia: a prospective cohort study. Issue 5 (31st May 2022) - Uldbjerg, Cecilie S.; Wilson, Louise F.; Koch, Trine; Christensen, Jane; Dehlendorff, Christian; Priskorn, Lærke; Abildgaard, Julie; Simonsen, Mette K.; Lim, Youn-Hee; Jørgensen, Jeanette T.; Andersen, Zorana J.; Juul, Anders; et al.
Abstract: Objective: Globally, dementia disproportionally affects women, which is not fully explained by higher female longevity. Oophorectomy at any age leads to the permanent loss of ovarian sex steroids, potentially increasing the risk of dementia. We aimed to investigate the association between oophorectomy and dementia and whether this was conditional on age at oophorectomy, hysterectomy or use of hormone therapy (HT). Methods: A prospective study of 24, 851 female nurses from the Danish Nurse Cohort. Nurses were followed from age 60 years or entry into the cohort, whichever came last, until date of dementia, death, emigration or end of follow-up (December 31, 2018), whichever came first. Poisson regression models with log-transformed person-years as offset were used to estimate the associations. Results: During 334, 420 person-years of follow-up, 1, 238 (5.0%) nurses developed dementia and 1, 969 (7.9%)/ 1, 016 (4.1%) contributed person-time after bilateral-/unilateral oophorectomy. In adjusted analyses, an 18% higher rate of dementia was observed following bilateral oophorectomy (aRR 1.18: 95% CI, 0.89-1.56) and 13% lower rate (aRR 0.87: 95% CI, 0.59-1.23) following unilateral oophorectomy compared to nurses who retained their ovaries. Similar effects were detected after stratification according to age at oophorectomy. No statistically significant modifying effects of hysterectomy or HT were detected ( P interaction ≥0.60). Conclusions: Bilateral, but not unilateral, oophorectomy was associated with an increased rate of incident dementia. We were unable to establish whether this association was conditional on hysterectomy or HT use. Although an increase in dementia after bilateral oophorectomy is biologically plausible, limited statistical power hampers the precision of the estimates.